Cystic Adenomyoma in Pregnancy: A Case Report - Verta S; Brambs CE; Christmann C (Dove Medical Press, 2024)
Stephanie Verta, Christine E Brambs, Corina Christmann Department of Obstetrics and Gynecology, Lucerne Cantonal Hospital, Lucerne, SwitzerlandCorrespondence: Stephanie Verta, Department of Obstetrics and Gynecology, Lucerne Cantonal Hospital, Lucerne, Switzerland, Tel +41 41 205 28 16, Email stephanie.verta@luks.chAbstract: Cystic adenomyomas (CA) are rare. They primarily affect adolescents and young women in their fertile years. Therefore, fertility and pregnancy outcome are of pivotal relevance in this patient collective. Apart from the guidelines of the European Society of Human Reproduction and Embryology (ESHRE) on the management of endometriosis in general, there are no specific treatment recommendations for CA and, as far as our research shows, no data illustrating the behavior of a CA over the course of pregnancy. Thus, we report the case of a 32-year-old 1-gravida, 1-para, preconceptionally diagnosed with a CA by ultrasound. After thoroughly discussing further treatment options, the decision was made to opt for a more conservative approach and not perform surgery before attempting a next pregnancy. The patient conceived spontaneously and sonographic monitoring of the CA throughout pregnancy showed complete regression of the cystic component during the second trimester. A healthy baby was delivered at term by an uncomplicated elective cesarean section. Following a review of the literature and taking into account the course of our case, we propose the feasibility of a conservative, non-surgical approach in women with a CA and the desire to conceive.Keywords: cystic adenomyoma, endometriosis, conservative management, pregnancy, fertility